BEHAVIOUR BIAS IN INVESTMENT DECISIONS: EMPIRICAL STUDY OF INVESTOR PSYCHOLOGY IN INDONESIA - Deddy Marciano; Zunairoh Zunairoh; Liliana Inggrit Wijaya (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
Investing involves putting money into a variety of asset classes for a predetermined amount of time in the hopes of increasing total value and producing more income. The goals of investments and economics, such as value creation, profit generation, and other related goals, are strongly correlated. It is critical to recognize that investments may include additional financial, social, and spiritual goals. This research aims to assess investor behavior from internal and external perspectives concerning investing decisions. This study employs the Structural Equation Model (SEM) methodology utilizing the Smart-PLS software. This study's findings demonstrate that qualities including anger, anxiety, overconfidence, and self-monitoring positively influence investment decisions. Herding mitigates the adverse impacts of anger, anxiety, overconfidence, and self-monitoring on investment decisions. This research's consequences can assist investors in circumventing irrational risks and yield more objective findings grounded in thorough study. This tendency can result in inefficient market transactions, asset bubbles, and significant volatility. This study arose as a counter to the conventional understanding of exchange markets predicated on the premise of trader rationality. This research identifies that emotional emotions, risk perception, and cognitive biases frequently affect investment decisions by comprehending human nature.